2016
DOI: 10.1038/srep26611
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered pre-microRNA-34a prodrug suppresses orthotopic osteosarcoma xenograft tumor growth via the induction of apoptosis and cell cycle arrest

Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumor in children, and microRNA-34a (miR-34a) replacement therapy represents a new treatment strategy. This study was to define the effectiveness and safety profiles of a novel bioengineered miR-34a prodrug in orthotopic OS xenograft tumor mouse model. Highly purified pre-miR-34a prodrug significantly inhibited the proliferation of human 143B and MG-63 cells in a dose dependent manner and to much greater degrees than controls, which was attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 50 publications
6
49
0
Order By: Relevance
“…Bioengineered miR-34a has showed to decrease the expression of c-Met and inhibited OS cell growth and invasion by inducing apoptosis and cell cycle arrest. This study confirmed the effectiveness and safety of bioengineered miR-34a using an orthotopic OS xenograft tumor mouse model (Zhao et al, 2016). Another study showed an inverse relationship between the expression of miR-34a-5p and c-Met in bone metastasis, but not in non-metastatic or metastatic breast carcinomas (Maroni et al, 2017).…”
Section: Mirna-34 Family and C-metsupporting
confidence: 74%
“…Bioengineered miR-34a has showed to decrease the expression of c-Met and inhibited OS cell growth and invasion by inducing apoptosis and cell cycle arrest. This study confirmed the effectiveness and safety of bioengineered miR-34a using an orthotopic OS xenograft tumor mouse model (Zhao et al, 2016). Another study showed an inverse relationship between the expression of miR-34a-5p and c-Met in bone metastasis, but not in non-metastatic or metastatic breast carcinomas (Maroni et al, 2017).…”
Section: Mirna-34 Family and C-metsupporting
confidence: 74%
“…Likewise, systemic delivery of an improved miR-34a-5p prodrug significantly decreased metastatic lung xenograft tumor growth in mice (Ho et al, 2018). In addition, other formulation of miR-34a prodrugs have resulted in similar findings in orthotopic osteosarcoma xenograft tumor mouse model (Zhao et al, 2016) and in combination therapy to reduce pulmonary metastases and osteosarcoma progression (Jian et al, 2017). In both these studies, it was also shown that the therapeutic doses of mir-34a prodrug were well-tolerated as indicated in blood chemistry profiles monitoring for hepatic and renal toxicities.…”
Section: Berasmentioning
confidence: 85%
“…Because some miRNAs regulate genes underlying drug metabolism and disposition (Yu, 2009;Ingelman-Sundberg et al, 2013;Yokoi and Nakajima, 2013;Yu et al, 2016), it is essential to evaluate possible DDIs in vivo for safety reasons. Recently, our group engineered a biologic miR-34a prodrug whose mechanistic actions on target gene expression and xenograft tumor progression have been documented Zhao et al, 2015Zhao et al, , 2016. In this study, we elucidated the effects of biologic miR-34a on the PK of five P450 probe drugs after we established and validated a general, rapid, and practical single-mouse PK approach.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miR-34a agents may be reintroduced into tumor cells to control tumor progression and metastasis. Recently, our group bioengineered a chimeric miR-34a agent and demonstrated that this biologic miR-34a prodrug is effective to suppress miR-34a target gene expression, inhibit human carcinoma cell proliferation and invasion, and reduce tumor growth in subcutaneous and orthotopic xenograft mouse models Zhao et al, 2015Zhao et al, , 2016. However, it is unknown whether therapeutic miR-34a would cause significant drugdrug interactions (DDIs), which are a critical component in drug development, particularly for combination therapy.…”
Section: Introductionmentioning
confidence: 99%